PLANNING AND FEASIBILITY STUDY OF A HYBRID SOLAR POWER PLANT WITH AN ADDED AUTOMATIC TRANSFER SWITCH (ATS) FOR AN OFFICE BUILDING - Chandra Buana; Muhammad Yusuf Yunus; Muhammad Daffa Abbas; Rizal Ashari; Nita Sri Indah Sari (Universitas Mercu Buana, 2023)
The Office of the Regent of Sidenreng Rappang (Sidrap), situated on Harapan Baru Street, Batu Lappa, Watang Pulu District, Sidrap Regency, South Sulawesi, consumes 200 kWh of electricity daily for lighting, resulting in substantial energy costs. Recognizing the potential for renewable energy, especially with a daily solar radiation potential of 5.8 kWh/m2, this study proposes the implementation of a hybrid solar power plant system. The system incorporates Photovoltaic (PV) as the primary energy source, with the Grid and Generator serving as backup sources through an AC Coupling configuration utilizing Automatic Transfer Switch (ATS). The research employs a simulation approach using HOMER Pro software for system modeling, SketchUp software for solar panel layout, AutoCAD software for ATS circuit modeling, and theoretical calculations for financial analysis. The results indicate a solar power plant capacity of 39.6 kW, producing 75,701 kWh/year with an impressive 83.3% renewable penetration. From an economic standpoint, the project requires an investment of IDR 642,714,960, with a net present cost of IDR 1,573,177,823, and a cost of energy value of IDR 1,401.38/kWh. In terms of feasibility, the project demonstrates a net present value exceeding zero (IDR 216,680,041), a profitability index greater than one (1.33), an internal rate of return surpassing the credit interest rate (12.488%), and a payback period of 7 years and 7 months. These findings affirm the feasibility of the hybrid solar power plant planning project for the Sidrap Regent's Office, showcasing its economic viability and potential for sustainable energy solutions.